2017
DOI: 10.1093/bjsw/bcx070
|View full text |Cite
|
Sign up to set email alerts
|

Commonalities and Differences in Social Work with Learning Disability and Child Protection: Findings from a UK ‘Burnout’ National Survey

Abstract: Social work with adults with learning disabilities or intellectual disability may be organised as a discrete or specialist area of practice in the United Kingdom (UK). Little is known about contemporary social work practitioners' views of their work with adults with learning disabilities and if these differ from those of social workers in practice with different user groups or working in other specialities. This paper reports findings from a national survey of UK social workers undertaken in 2015 that measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The more vulnerable and emotionally presented the service users are the more challenging the relationship with the professional SW is, with higher potential of emotional fatigue. This can explain higher prevalence of stress and burnout observed among SWs providing support to children and adults with learning disabilities and mental health needs than SWs working with other client groups (Hussein et al 2014a , b ; Edwards et al 2010 ; Evans et al 2006 ; Hamama 2012 ; McFadden et al 2017 ). CFSWs could thus be theorized to face additional stressors than other SWs due to concepts of ‘working alliance’ (Bordin 1979 ) and ‘emotional labour’ where the bond between client and SW can impact on professionals’ wellbeing and stress.…”
Section: Introductionmentioning
confidence: 99%
“…The more vulnerable and emotionally presented the service users are the more challenging the relationship with the professional SW is, with higher potential of emotional fatigue. This can explain higher prevalence of stress and burnout observed among SWs providing support to children and adults with learning disabilities and mental health needs than SWs working with other client groups (Hussein et al 2014a , b ; Edwards et al 2010 ; Evans et al 2006 ; Hamama 2012 ; McFadden et al 2017 ). CFSWs could thus be theorized to face additional stressors than other SWs due to concepts of ‘working alliance’ (Bordin 1979 ) and ‘emotional labour’ where the bond between client and SW can impact on professionals’ wellbeing and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout, as the behavioral manifestation of occupational stress, secondary traumatic stress (i.e., observable reactions that develop when working with people who have experienced trauma with symptoms characteristic of post-traumatic stress disorder [ 18 , 19 ]), and the vicarious trauma (i.e., personal behavioral and/or emotional changes that occur because of empathic involvement with people who have experienced trauma [ 19 ]), is a highly prevalent work-related stress reaction experienced in helping professions [ 20 ], including social policy professionals such as social workers [ 21 , 22 ]. One area where burnout is especially relevant is in child social work, having significant repercussions in its different dimensions on these workers [ 23 , 24 , 25 , 26 ] and persons with disabilities [ 27 ]. However, sometimes, these differences are minimal [ 28 ], and there is no worldwide universal pattern within social work that marks high rates of burnout.…”
Section: Introductionmentioning
confidence: 99%
“…One area for investigation in any such survey is whether having support from a manager with AMHP experience is effective. Using questions and measures that enabled comparison with other social work surveys would be of particular value (such as that by McFadden, Manthorpe, & Mulley, 2018).…”
Section: Further Research and Local Data Collectionmentioning
confidence: 99%
“…The limited amount of evidence about AMHP training, for which the most recent review occurred over six years ago by the then training regulator, the General Social Care Council (Jones et al, 2012), provides workforce planners with challenges. Jones et al's (2012) study reported broadly positive views, although the time commitment during secondment for training was seen as problematic by some candidates.…”
Section: Further Research and Local Data Collectionmentioning
confidence: 99%